AQ-10 Potential Animal Carriers Rabies (HPR) Suspect Arriving from Java to Sumatera - Basid Sastradiawan (Hemera Zoa, 2018)
Rabies is zoonotic disease that is still haunting in severel in Indonesia. Management of rabies, both eradcation and vaccination continues. However, cultural constraints and lack of understanding and concern of all stakeholders are their own obstacles in handling and controlling this disease.The number of 102 titers of antibodies obtained in the HPR that were transversed from Java to Sumatera became an early warning, that the rabies control and eradication program on the island of Sumatera will experience difficulties.Support from all stakeholders to realize Sumatera free of rabies is no longer negotiable. The local government, police, Quarantine and community are the pioneers of success of the Sumatera-free rabies program. Without the synergy of the parties involved, the Sumatera-free Rabies program is just a dream.